Human posture recognition : literature review - Khalifa, Othman Omran; Htike, Kyaw Kyaw; Lai, Weng Kin; Alkhazmi, A. A. (IIUM Press, 2011)
Human Posture giving machines the ability to detect, track and idenlify people and their actions from video. has become a central topic in computer vision research. Recognition of human posture is a very challenging problem. The importance of human posture recognition or c1assification is evident by the incrcasing requiremcnt of machines that are able to interact intelligently and effortlessly with a human inhabiled environment. Recognizing human posture in image and video is an important task in many multimedia applicalions. such as multimedia information retrieval, human computer interaction, and surveillance.Posture is a snapshot of human body configuration, Many research work focus on human action recognition which corresponds to the analysis of human motion. Thereby spatial and temporal characteristics of an object need to be considered. The estimation of the human body posture and the localization of the body parts is one way to analyze the spatial part.